Analisis Hukum General Data Protection Regulation (GDPR) Terhadap Data Pribadi Konsumen Dalam Melakukan Transaksi Online - Yahya Ziqra; Sunarmi Sunarmi; Mahmul Siregar; Jelly Leviza (Iuris Studia: Jurnal Kajian Hukum, 2021)
Privacy is very important for individuals because basically a person must have a side of himself that others do not want to know and there will be a desire from the individual to protect his secrets. European Union (EU) law views personal data as any information relating to a living person that can be protected through the General Data Protection Regulation (GDPR). The purpose of this study is to find out why personal data needs legal protection, whether the laws and regulations in Indonesia have protected personal data in online transactions, and how the comparison of personal data protection in conducting online transactions in Indonesia with the European Union. This research method uses a descriptive normative juridical approach. The data used are secondary data collected by using library research techniques. All data were analyzed by qualitative data analysis method. Based on research, it is very important to protect personal data so that it is not easily exploited or misused when conducting online transactions, but the laws and regulations in Indonesia have not fully protected personal data.